Brucelosis en niños: Presentación inusual de dos casos. - Tori, Carlos (2013)
Even though brucellosis in our country is an endemic disease, it is more commonly seen over the age of ten years. We here present two cases of children whose ages eighteen months and two years respectively. It is interesting the way both patients began their disease, with acute pharingitis and exudative amigdalitis, signs that are poorly emphasized in the literature, and that accounts for the fact that many of them are treated initially for a respiratory infection